Mental Revolution in Catholic Religious Education Learning Based on the Laudato Si' Curriculum - Hermania Bhoki; Emiliana Sri Pudjiarti (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This study aims to analyze how the teacher's role in voluntarily doing new evangelization as a mediating variable between the teacher's professional competence and On the Care for Our Common Home ecotheological commitment. This study used a quantitative approach. The study population was all elementary-level Catholic religious education teachers in East Flores District. The sample was 110 Inpres Elementary School teachers, 128 Catholic Elementary School teachers and 44 Public Elementary Schools for a total of 282 teachers. Data collection used a questionnaire by utilizing google form. The data analysis technique used in this study is Structural Equation Model (SEM) using the statistical software AMOS version 22. The study findings revealed that Catholic religious education teachers' professional competence and eco-theological commitment could be a driving force in carrying out the most recent contextual new evangelization. It is beneficial for the new generation not to continue actions that cause environmental crises caused by adults. As a result, the earth can provide itself with a common home, a healthy, decent, and comfortable to live in for one big family consisting of all generations of living beings.